2019
DOI: 10.1080/23328940.2019.1617030
|View full text |Cite
|
Sign up to set email alerts
|

Heat-related issues and practical applications for Paralympic athletes at Tokyo 2020

Abstract: International sporting competitions, including the Paralympic Games, are increasingly being held in hot and/or humid environmental conditions. Thus, a greater emphasis is being placed on preparing athletes for the potentially challenging environmental conditions of the host cities, such as the upcoming Games in Tokyo in 2020. However, evidence-based practices are limited for the impairment groups that are eligible to compete in Paralympic sport. This review aims to provide an overview of heat-related issues fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 136 publications
1
56
0
Order By: Relevance
“…An understanding of the perceptual responses and subsequent time-course for adaptations is important for those prescribing HA, allowing perceived fatigue to be somewhat predicted and potentially mitigated. As such, our research supports anecdotal evidence of increased tiredness and lethargy following exercise-heat stress [10], which is important to consider when prescribing HA, such as that for the Tokyo 2020 Olympic and Paralympic Games [1,20]. The cumulative effect of combined stressors and progressive physiological strain (e.g.…”
Section: Applicationsupporting
confidence: 78%
“…An understanding of the perceptual responses and subsequent time-course for adaptations is important for those prescribing HA, allowing perceived fatigue to be somewhat predicted and potentially mitigated. As such, our research supports anecdotal evidence of increased tiredness and lethargy following exercise-heat stress [10], which is important to consider when prescribing HA, such as that for the Tokyo 2020 Olympic and Paralympic Games [1,20]. The cumulative effect of combined stressors and progressive physiological strain (e.g.…”
Section: Applicationsupporting
confidence: 78%
“…This review should direct practitioners preparing non-disabled individuals for competition in heat stress to the optimal methods to attenuate the heat-induced performance decrements and to protect athlete health. Whilst many thermophysiology principles are shared, we direct the reader to literature describing techniques to alleviate heat strain in para-athletes, given critical and pertinent nuances should be considered from health and performance perspectives in this cohort [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was shown that the decrease in the heart rate was significant in the pre-cooling and per-cooling groups compared to the control group. Pre-cooling causes blood vessels to constrict and reduce superficial blood flow, thereby lowering body temperature (19). Vascular contractions occur when the cold sends stimuli to adrenergic heat receptors in the skin, thus stimulating sympathetic fibers and creating stimulus reflex (20).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Zeus Analyzer 9.9 was used to measure body composition and fat percentage (Table 1) (18). A Beurer FT-70 digital thermometer, polar-FT60 heart rate monitoring, Microlife blood pressure monitoring, and ELISA technique were used to measure the core body temperature, heart rate, blood pressure, dopamine, cortisol, and lactate dehydrogenase, respectively (18,19). Subsequently, written and oral consent was obtained from the subjects.…”
Section: Methodsmentioning
confidence: 99%